Experimental study of the vibrational spectra of (CH3) 3GeBr supported by DFT calculations - Roldan, Maria Lorena (2009)
The infrared and Raman spectra of bromotrimethylgermane (BTMG) were recorded afresh to complete the assignment of its vibrational spectra. The vibrational spectrum of BTMG has been predicted from hybrid density functional theory calculations (B3LYP) with several basis sets. The resulting harmonic wavenumbers were scaled by Pulay's scaled quantum mechanical (SQM) and the wavenumber-Iinear scaling (WLS) methods to obtain accurate force fields which could aid in the wibrational assignment. Low-temperature infrared techniques together with Fourier self-deconvolution (FSD) on the Raman spectrum were used to improve the resolution of the spectra for the modes that could not be observed before. An SQM analysis was carried out to obtain the valence force constants and a set of scale factors that best reproduced the experimental data.